EFFICACY OF BREATHING TECHNIQUES FOR MANAGEMENT OF MATERNAL OUTCOMES DURING LABOR - SHAHEEN, T; ZIA, N; MUI, LG; NORDIN, R (Biological and Clinical Sciences Research Journal, 2024)
Maternal anxiety during labor can adversely affect both the mother and fetus. Effective management strategies, including non-pharmacological interventions like breathing patterns, are crucial to improving labor outcomes and maternal well-being. Objective: To evaluate the efficacy of breathing patterns for the management of maternal anxiety during the dilation phase of labor. Methods: A prospective study was conducted in the Physiotherapy and Obstetrics and Gynecology Department of DHQ Hospital from April 2023 to April 2024. One hundred fifty pregnant women in active labor with gestational ages of 37-41 weeks were included. The patients were divided into the study group (70 women) and the control group (80 women). The control group followed standard labor procedures, while the study group was guided on breathing patterns according to a specified protocol. The primary endpoint was maternal anxiety, and secondary endpoints included pain, fatigue, satisfaction, labor duration, and delivery mode. The 5-minute Apgar score was also assessed for the fetus. Statistical analysis was performed to compare outcomes between the groups. Results: Baseline maternal outcomes, including pain, fatigue, anxiety, satisfaction, and labor duration, showed no significant differences between the study and control groups. The mean labor duration was 7.70 ± 3.36 hours for the study group and 8.00 ± 2.54 hours for the control group, with a mean difference of 0.30 hours (95% CI 1.35-0.78). Maternal outcomes did not differ between groups after two hours of protocol implementation and sensitivity analysis. The delivery mode was similar in both groups, with a relative risk of 0.10 (95% CI 0.78-1.09) and 0.10 (95% CI 0.77-1.10) for protocol and sensitivity analysis, respectively. The 5-minute Apgar scores also showed no significant differences between the groups. Conclusion: Using breathing patterns during active labor did not significantly impact maternal outcomes, including pain, satisfaction, anxiety, and fatigue.